COVID-19 Vaccination During Pregnancy: Coverage and Safety. Issue 4 (21st December 2022) - Blakeway, H.; Prasad, S.; Kalafat, E.; Heath, P.T.; Ladhani, S.N.; Le Doare, K.; Magee, L.A.; O'Brien, P.; Rezvan, A.; von Dadelszen, P.; Khalil, A.
Abstract : ( Am J Obstet Gynecol . 2022;226:236.e1–14) While the pregnant population was not included in initial randomized controlled safety and efficacy trials of the COVID-19 vaccines, some limited data on the vaccine during pregnancy came from the CDC V-safe health checker, some inadvertent pregnancies in vaccine trials, and a formal pregnancy registry. While the COVID-19 vaccines do not contain a live virus and are theoretically considered safe in pregnancy, not all health care professionals have recommended routine vaccination since the start of vaccine rollout. This study examines the safety of COVID-19 in pregnant women, the rate of uptake, and outcomes of vaccinated pregnant individuals compared with the unvaccinated pregnant population.